Clinical effectiveness and cost-effectiveness of open and arthroscopic rotator cuff repair [the UK Rotator Cuff Surgery (UKUFF) randomised trial]. - Carr, A; Cooper, C; Campbell, M; Rees, J; Moser, J; Beard, D; Fitzpatrick, R; Gray, A; Dawson, J; Murphy, J; Bruhn, H; Cooper, D; et al. (NIHR Health Technology Assessment Programme, 2015)
BACKGROUND: Uncertainty exists regarding the best management of patients with degenerative tears of the rotator cuff. OBJECTIVE: To evaluate the clinical effectiveness and cost-effectiveness of arthroscopic and open rotator cuff repair in patients aged ≥ 50 years with degenerative rotator cuff tendon tears. DESIGN: Two parallel-group randomised controlled trial. SETTING: Nineteen teaching and district general hospitals in the UK. PARTICIPANTS: Patients (n = 273) aged ≥ 50 years with degenerative rotator cuff tendon tears. INTERVENTIONS: Arthroscopic surgery and open rotator cuff repair, with surgeons using their usual and preferred method of arthroscopic or open repair. Follow-up was by telephone questionnaire at 2 and 8 weeks after surgery and by postal questionnaire at 8, 12 and 24 months after randomisation. MAIN OUTCOME MEASURES: The Oxford Shoulder Score (OSS) at 24 months was the primary outcome measure. Magnetic resonance imaging evaluation of the shoulder was made at 12 months after surgery to assess the integrity of the repair. RESULTS: The mean OSS improved from 26.3 [standard deviation (SD) 8.2] at baseline to 41.7 (SD 7.9) at 24 months for arthroscopic surgery and from 25.0 (SD 8.0) at baseline to 41.5 (SD 7.9) at 24 months for open surgery. When effect sizes are shown for the intervention, a negative sign indicates that an open procedure is favoured. For the intention-to-treat analysis, there was no statistical difference between the groups, the difference in OSS score at 24 months was -0.76 [95% confidence interval (CI) -2.75 to 1.22; p = 0.452] and the CI excluded the predetermined clinically important difference in the OSS of 3 points. There was also no statistical difference when the groups were compared per protocol (difference in OSS score -0.46, 95% CI -5.30 to 4.39; p = 0.854). The questionnaire response rate was > 86%. At 8 months, 77% of participants reported that shoulder problems were much or slightly better, and at 24 months this increased to 85%. There were no significant differences in mean cost between the arthroscopic group and the open repair group for any of the component resource-use categories, nor for the total follow-up costs at 24 months. The overall treatment cost at 2 years was £2567 (SD £176) for arthroscopic surgery and £2699 (SD £149) for open surgery, according to intention-to-treat analysis. For the per-protocol analysis there was a significant difference in total initial procedure-related costs between the arthroscopic group and the open repair group, with arthroscopic repair being more costly by £371 (95% CI £135 to £607). Total quality-adjusted life-years accrued at 24 months averaged 1.34 (SD 0.05) in the arthroscopic repair group and 1.35 (SD 0.05) in the open repair group, a non-significant difference of 0.01 (95% CI -0.11 to 0.10). The rate of re-tear was not significantly different across the randomised groups (46.4% and 38.6% for arthroscopic and open surgery, respectively). The participants with tears that were impossible to repair had the lowest OSSs, the participants with re-tears had slightly higher OSSs and the participants with healed repairs had the most improved OSSs. These findings were the same when analysed per protocol. CONCLUSION: In patients aged > 50 years with a degenerative rotator cuff tear there is no difference in clinical effectiveness or cost-effectiveness between open repair and arthroscopic repair at 2 years for the primary outcome (OSS) and all other prespecified secondary outcomes. Future work should explore new methods to improve tendon healing and reduce the high rate of re-tears observed in this trial. TRIAL REGISTRATION: Current Controlled Trials ISRCTN97804283. FUNDING: This project was funded by the National Institute for Health Research Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 19, No. 80. See the NIHR Journals Library website for further project information.